2008
DOI: 10.1103/physrevc.77.054312
|View full text |Cite
|
Sign up to set email alerts
|

Lowest eigenvalues of random Hamiltonians

Abstract: In this paper we present results of the lowest eigenvalues of random Hamiltonians for both fermion and boson systems. We show that an empirical formula of evaluating the lowest eigenvalues of random Hamiltonians in terms of energy centroids and widths of eigenvalues are applicable to many different systems (except for d boson systems). We improve the accuracy of the formula by adding moments higher than two. We suggest another new formula to evaluate the lowest eigenvalues for random matrices with large dimens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
1
16
1
Order By: Relevance
“…13 This prediction is consistent with molecular dynamics simulations for the Lennard-Jones system (where the stable phase is fcc), where the subcritical crystalline fluctuations have the metastable bcc structure, while the critical fluctuation has an fcc core surrounded by a bcc-like surface layer. 14 Composite bcc/fcc nuclei have also been predicted by the density functional theory 15 and a Ginzburg-Landau free energy based phase-field theory. 4 Experiments on globular proteins have shown that a metastable critical point in the supersaturated liquid may help the formation of crystal nuclei via liquid phase separation, leading to composite nuclei of crystal surrounded by dense liquid, 16 a finding recovered by computer simulations 17 and density functional/phasefield computations.…”
Section: Introductionmentioning
confidence: 93%
“…13 This prediction is consistent with molecular dynamics simulations for the Lennard-Jones system (where the stable phase is fcc), where the subcritical crystalline fluctuations have the metastable bcc structure, while the critical fluctuation has an fcc core surrounded by a bcc-like surface layer. 14 Composite bcc/fcc nuclei have also been predicted by the density functional theory 15 and a Ginzburg-Landau free energy based phase-field theory. 4 Experiments on globular proteins have shown that a metastable critical point in the supersaturated liquid may help the formation of crystal nuclei via liquid phase separation, leading to composite nuclei of crystal surrounded by dense liquid, 16 a finding recovered by computer simulations 17 and density functional/phasefield computations.…”
Section: Introductionmentioning
confidence: 93%
“…Using (5) repeatedly to replace d + i|ψ w in (4) by γ |ψ w , we obtain readily the effective Hamiltonian H…”
Section: Linear Correlation Between Eigenvalues and Diagonal Matrix Ementioning
confidence: 99%
“…Papenbrock et al [2,5] suggested statistical correlation between the spectral radius and the spectral width in evaluating spin I ground state probability in the presence of random two-body interactions. Along the same line, Yoshinaga et al [6,7] studied the lowest energy of spin I states by the moments of energy spectra based on the fact that the eigenvalues of Hamiltonian under two-body random ensemble follow the Gaussian distribution [8,9] . Recently, we found linear (statistical) correlation between eigenvalues and diagonal matrix elements in the nuclear shell model Hamiltonian [10,11] .…”
mentioning
confidence: 99%